Media, Big men and Power Struggles in Football Bodies: Framing the Impasse between the ZIFA and PSI leadership in Selected Media - Bare, Kudzai Sheryl; Ncube, Lyton; Chibuwe, Albert (Critical arts, 2021)
Power struggles, factionalism and chaos in football management bodies are a common phenomenon in Zimbabwe. Journalists and the media play a crucial role in these power struggles. However, growing literature on communication and sport in Zimbabwe has under-theorised the subject. Deploying framing theory lens, this research explores the media's reportage of the "fights" between the Zimbabwe Football Association (ZIFA) leadership and their biggest affiliate-the Premier Soccer League (PSL). Focus is on the period when politician-cum-businessman Phillip Chiyangwa served as ZIFA president (2015-2018). Stories for analysis were purposively selected from The Herald and the Newsday. The former is state controlled while the latter is privately owned. In-depth interviews were also conducted with selected sports journalists from the two publications to establish forces behind the positions adopted by the media organisations during the period under study. By demonstrating that 'big men' rely on the media to outmaneouvre rivals, the article makes the argument that the two newspapers were complicit in the mediatization of the power struggles between ZIFA and PSL leadership. Critically, due to multidimensional forms of capture, The Herald and Newsday became sycophantic in their framing of the ZIFA and PSL dispute.